Solvent-mediated extraction of fatty acids in bilayer oil paint models: a comparative analysis of solvent application methods - Baij, Lambert; Astefanei, Alina; Hermans, Joen; Brinkhuis, Francine; Groenewegen, Heleen; Chassouant, Louise; Johansson, Sofia; Corthals, Garry; Tokarski, Caroline; Iedema, Piet; Keune, Katrien (Heritage science, 2019)
The impact of solvent exposure on oil paintings and the differences between solvent application methods are longstanding topics in cleaning studies. Solvent exposure is ideally kept to a minimum, because solvent swelling can lead to the extraction and displacement of reactive paint components. In particular, important concerns are fatty acids displacement resulting in metal soap formation and embrittlement of paint due to solvent exposure. In this study, the extraction of a saturated fatty acid (SFA) marker and the formation of zinc soaps were monitored to measure the impact of solvent cleaning on tailored bilayer model systems for aged oil paint. Three methods of solvent application were compared: cotton swab, rigid gel and Evolon tissue (with different solvent loading). The samples were analysed by surface acoustic wave nebulization mass spectrometry (SAWN-MS) and thermally-assisted hydrolysis and methylation pyrolysis gas chromatography mass spectrometry (THM-Py-GC/MS) by comparing the calculated margaric:palmitic acid ( C 17 : C 16 ) ratio determined in the extracts (taken from the swab, gel or Evolon tissue). We conclude that both swab cleaning and squeezed Evolon tissue application result in comparable SFA extraction. The rigid gel and Evolon with controlled solvent-loading limit the amount of SFA extraction. The distribution of C 17 after solvent application was visualised using static Time-of-Flight Secondary Ion Mass Spectrometry (ToF-SIMS) on cross sections, showing that C 17 redistribution took place in all cases where solvent was applied. Crystalline zinc soaps formation was not observed after 5 min of ethanol exposure in the embedded cross-sections with imaging ATR-FTIR, indicating that solvent exposure does not immediately trigger the formation of crystalline metal soaps. However, significant zinc soap formation was found after 30 min of ethanol exposure using Evolon tissue without controlled loading. This study contributes to a better understanding of the impact of different methods of solvent application on oil paintings and highlights important differences between these methods.